Menuju Equilibrium: Pengintegrasian Makna Teologis pada Budaya Madundum Banua - Jekson Berdame; David Rade Manat Simanjuntak; Ryanto Adilang; Junaydi Jufriadi Lempoy; Tifany Fergie Tombokan (STT Bala Keselamatan Palu, 2022)
Abstrak: Madandum Banua is a culture carried out by the people of Dapihe Village, Talaud Islands Regency, which aims to expel riwu (seasonal diseases) or things that are considered odd by the local community through a ritual led by Ratumbanua or Inangguwanua on a large rock called Batu Tarenggo or Watum'barian. The existence of Christianity in Talaud Islands Regency as the majority religion is slowly starting to displace the existence of Madandum Banua. The labeling of syncretism towards the implementation of this culture certainly makes the congregation start to be reluctant and feel afraid in reflecting and implementing this culture. On the other hand, the government continues to encourage people who are also members of the congregation to preserve the culture of Madandum Banua by providing subsidies and establishing traditional groups. This situation shows that there is a struggle and clash of values between Christianity and the culture of Madandum Banua, which makes congregation members feel confused and in a dilemma. Through this paper, burapaya researchers seek common ground or balance (equilibrium) between the two values, namely by integrating theological meaning into the culture of Madandum Banua. The contextual theology approach of the translation model is used as an entry point in understanding the culture of Madandum Banua and interpreting theological values in that culture, so that the integration process can take place in a balanced way. In the end, it is hoped that writing will be an alternative for congregation members in responding to the circumstances experienced when practicing and preserving the madundum banua culture in accordance with government recommendations and avoiding the stigmatization of syncretism produced by the church. Abstrak: Madandum Banua merupakan budaya yang dilakukan masyarakat desa Dapihe Kabupaten Kepulauan Talaud yang bertujuan untuk mengusir riwu (penyakit musim) atau hal-hal yang dianggap janggal oleh masyarakat setempat melalui ritual yang dipimpin oleh Ratumbanua atau Inangguwanua di sebuah batu besar yang di sebut dengan batu Tarenggo atau Watum’barian. Keberadaan kekristenan di Kabupaten Kepulauan Talaud sebagai agama mayoritas secara perlahan mulai menggusur eksistensi Madandum Banua. Pelebelan sinkretisme terhadap pelaksanaan budaya ini tentunya membuat jemaat mulai enggan dan merasa takut dalam merefleksikan dan melaksnakan budaya ini. Di sisi lain, pihak pemerintah terus mendorong masyarakat yang sekaligus anggota jemaat untuk melestarikan budaya Madandum Banua dengan memberikan subsidi dan pendirian kelompok adat. Keadaan ini menunjukan adanya pertarungan dan benturan nilai antara kekristanan dan budaya Madandum Banua sehingga membuat anggota jemaat merasa binggung serta dilematis. Melalui tulisan ini, peneliti burapaya mencari titik temu atau kesimbangan (equilibrium) antar kedua nilai tersbut yaitu dengan cara mengintegrasikan makna teologi pada budaya Madandum Banua. Pendekatan teologi kontekstual model terjemahan digunakan sebagai pintu masuk dalam memahami budaya Madandum Banua dan memaknai nilai teologis pada budaya tersebut, sehingga proses integrasi dapat berlangsung dengan seimbang. Pada akhirnya tulisan diharapkan mampu menjadi alternatif bagi anggota jemaat dalam merespon keadaan yang dialami ketika mempraktikan dan melestarikan budaya madundum banua sesuai dengan anjuran pemerintah dan terhindar dari stikmatisasi sinkretisme yang diproduksi oleh gereja.